Principles of 3D Image Analysis and Synthesis - Girod, Bernd; Greiner, Günther; Niemann, Heinrich (The Springer International Series in Engineering and Computer Science, 2002)
Traditionally, say 15 years ago, three-dimensional image analysis (aka computer vi sion) and three-dimensional image synthesis (aka computer graphics) were separate fields. Rarely were expert